2022
DOI: 10.1007/s10608-022-10330-z
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Anhedonia in Major Depressive Disorder with Future Event Specificity Training (FEST): A Randomized Controlled Trial

Abstract: Background Improving future thinking, such as characteristics of specificity, detail, and use of mental imagery, may be one means to reduce anhedonia, particularly in a Major Depressive Episode (MDE) in which future thinking is impaired. The current study aimed to test this using a validated program, Future Event Specificity Training (FEST). Methods Participants (N = 177; 80.8% women; M age = 43.7, SD = 11.8) with a current depressive episode with anhedoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 83 publications
2
9
0
Order By: Relevance
“…The effect sizes reported by Taylor et al [29] based on different situations were 0.72 to 1.28. Also, in the research conducted by Hallford et al [30], the results showed that future event speci city training (FEST) can signi cantly reduce anhedonia. Therefore, it seems that the group CBT + CRT manual was able to reduce the anhedonia by increasing the experience of pleasure.…”
Section: Discussionmentioning
confidence: 95%
“…The effect sizes reported by Taylor et al [29] based on different situations were 0.72 to 1.28. Also, in the research conducted by Hallford et al [30], the results showed that future event speci city training (FEST) can signi cantly reduce anhedonia. Therefore, it seems that the group CBT + CRT manual was able to reduce the anhedonia by increasing the experience of pleasure.…”
Section: Discussionmentioning
confidence: 95%
“…A preliminary study reported beneficial effects for a different type of cognitive intervention that uses mental imagery to anticipate and experience pleasure in future activities. Although suggestive, a larger, better controlled study is needed (47).…”
Section: Common Residual Symptomsmentioning
confidence: 99%
“…The EFT training usually invites subjects to imagine positive‐valenced future events. Evidence suggests that, after EFT training, patients with MDD have improved future thinking characteristics, reduced anhedonia, increased anticipatory and anticipated pleasure for future events, and increased behavioral activation and functioning (Hallford et al, 2022). In schizophrenia patients, EFT training can improve MTT specificity and reduce depressive symptoms (Chen et al, 2020).…”
Section: Interventions For Mtt Impairmentsmentioning
confidence: 99%